More than just life and death: advances in imaging and analysis for 3D-bioprinted tissues - Spiller, Erin; Duarte Campos, Daniela Filipa (Frontiers in Bioengineering and Biotechnology, 2025)
3D bioprinting is a fast-growing field with applications in both microphysiological systems and tissue engineering. However, the qualifications and definitions of success for 3D-bioprinted products are insufficient. We can further our characterization of 3D-bioprinting methods and finished products using new imaging techniques and analysis methods, including the use of AI tools. This multi-faceted approach can deepen our understanding of valuable technology by examining the effects of 3D bioprinting on cell identity, behavior and organelles. Defining a successful 3D-bioprinted product in addition to viability is crucial in the push toward using these models for drug screening or disease modeling, where robust and high-quality systems are required for meaningful data output.
Gesehen am 27.10.2025